Tailored smart bioactive glass nanoassembly for dual antibiotic in vitro sustained release against osteomyelitis. Issue 47 (15th November 2016) - Gupta, Nidhi; Santhiya, Deenan; Aditya, Anusha
Abstract : The effect of cetyltrimethylammonium bromide (CTAB) concentration as a sacrificial template on tunable mesostructure textured bioactive glass nanoparticles has been explored and characterized for osteomyelitis applications. Abstract : The effect of cetyltrimethylammonium bromide (CTAB) concentration as a sacrificial template on tunable mesostructure textured bioactive glass nanoparticles has been explored and characterized. For the 10 mM CTAB concentration templated sample, smart bioactive glass nanoassembly (nBGA) has been tailored for dual antibiotic sustained release against osteomyelitis disease. The loading of two different drugs on the bioglass has been controlled through a thin chitosan sheath. To our knowledge, for the first time synergistic co-drug delivery of two antibiotics, namely sodium ampicillin and gentamicin sulfate, through bioglass nanoassembly, along with bone regeneration has been considered. Sustained co-release kinetics of dual anti-biotic drugs at different time points was evaluated. In addition to this, the in situ loss in bacterial viability with time of the dual drug loaded bioglass nanoassembly has been quantified against two different mono- and co-bacterial cultures by live/dead BacLight bacterial viability kit. Additionally, osteoblast like osteosarcoma cells proliferation on the dual drug loaded bioglass nanoassembly surface has been quantified in the presence and absence of bacterial challenge. This study provides a new insight into the application of bioactive glass as an efficient co-drug delivery vehicle for osteomyelitis.